2004
DOI: 10.1529/biophysj.103.030627
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Self-Assembled Phospholipid Membrane Supported on Lipobeads

Abstract: The overall objective of our work was to make a hydrogel-supported phospholipid bilayer that models a cytoskeleton-supported cell membrane and provides a platform for studying membrane biology. Previously, we demonstrated that a pre-Lipobead, consisting of phospholipids covalently attached to the surface of a hydrogel, could give rise to a Lipobead when incubated with liposomes because the attached phospholipids promote self-assembly of a phospholipid membrane on the pre-Lipobead. We now report the properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…In many SPBs, however, slower lateral diffusion is typically observed. 58 In our Lipogels, the lipid bilayer coating may well not be smooth but rather may be corrugated because of imperfections in, and the finite thickness of, the shell region, which produces, in turn, a nonplanar distribution of hydrophobic anchor positions. Such corrugations would yield a slower apparent lateral diffusion coefficient overall.…”
Section: Scheme 1 Hydrophobic Modification Of Microgels Scheme 2 Famentioning
confidence: 99%
“…In many SPBs, however, slower lateral diffusion is typically observed. 58 In our Lipogels, the lipid bilayer coating may well not be smooth but rather may be corrugated because of imperfections in, and the finite thickness of, the shell region, which produces, in turn, a nonplanar distribution of hydrophobic anchor positions. Such corrugations would yield a slower apparent lateral diffusion coefficient overall.…”
Section: Scheme 1 Hydrophobic Modification Of Microgels Scheme 2 Famentioning
confidence: 99%
“…1 Since this discovery, a great deal of research interest has focused on the development of biomimetic supported bilayer systems incorporating various polymeric, ceramic, and functionalized substrates [2][3][4][5][6][7][8][9][10][11] for the introduction of membrane proteins for bio-and chemical sensing, drug discovery and delivery, and fundamental biophysical studies in near-native environments.…”
Section: Introductionmentioning
confidence: 99%
“…1A). More recently, we have confirmed that the Lipobead membrane is composed mostly of two leaflets of phospholipid and has the ability to encapsulate large hydrophilic solutes [8]. In the present study, we were interested in determining whether transmembrane receptors could be incorporated onto the surface of these Lipobeads and retain native function.…”
Section: Introductionmentioning
confidence: 94%